Effect on Neonatal Outcome of Pharmacological Interventions for Attenuation of the Maternal Haemodynamic Response to Tracheal Intubation: A Systematic Review. Issue 3 (May 2018) - Aman, A.; Salim, B.; Munshi, K.; Raza, S. A.; Khan, F. A.
The primary aim of this systematic review was to assess the effect on neonatal outcome of pharmacological interventions used for attenuation of the haemodynamic response to tracheal intubation in patients undergoing caesarean Section under general anaesthesia. A systematic search of randomised controlled trials from 1990 to 2015 was conducted. The primary outcome measure was the Apgar score at five minutes and secondary outcomes were umbilical arterial blood gas parameters and neurological adaptive capacity scores. Twenty-seven randomised controlled trials (1, 689 patients) were included in the qualitative synthesis. Only five studies using opioids (383 patients) and five studies using non-opioid analgesics (358 patients) were subjected to meta-analysis. The Apgar score at five minutes was significantly lower in neonates of opioid-treated mothers (mean difference: −0.29, 95% confidence interval −0.56 to −0.02, P-value=0.03) compared to mothers in the control group; the umbilical arterial pH was lower and there was a higher requirement for tactile stimulation in neonates. No difference was seen in Apgar scores of neonates of mothers administered non-opioid analgesics compared to placebo. No difference was observed in other parameters between opioid- or non-opioid-treated mothers. This review suggests that opioid interventions for attenuation of the haemodynamic response to tracheal intubation in pregnant patients under general anaesthesia affect neonatal Apgar scores at five minutes in neonates but the difference did not appear to be clinically meaningful. We were unable to demonstrate any difference in safety.